Effect of Calcium Carbonate on the Mechanical Properties and Microstructure of Red Clay - Lijie Chen; Xuejun Chen; Xin Yang; Pengyan Bi; Xiang Ding; Xiang Huang; He Wang (Advances in Materials Science and Engineering)
The influence of precipitated calcium carbonate on the strength and microstructure of red clay was studied. Precipitated calcium carbonate was added to red clay at ratios of 0%, 5%, 10%, 15%, and 20%. Shear tests were carried out on the samples to observe the effect of calcium carbonate on the mechanical properties of red clay. The results showed that, with increasing calcium carbonate content, the strength of red clay first decreased and then increased. The maximum strength was obtained for the sample with 20% calcium carbonate. Scanning electron microscopy (SEM) was used to observe the changes in microstructure caused by addition of calcium carbonate. The pores and cracks analysis system (PCAS) was used to quantitatively characterize the microstructure changes detected in SEM images. The addition of calcium carbonate decreased the pore area and increased the total number of pores of red clay. The incorporation of calcium carbonate caused the red clay particles to agglomerate. The higher the calcium carbonate content, the stronger the agglomeration of red clay particles in the soil samples.